2011
DOI: 10.2174/187152011795677454
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Signaling as a Therapeutic Target in Pancreatic Cancer

Abstract: Insulin-like growth factor-1 (IGF-1) leads via its receptor IGF-1R to the activation of the PI3K/Akt pathway, providing antiapoptotic signals to pre-malignant and malignant cells. In pancreatic cancer, IGF-1 and its receptor are constitutively overexpressed. Mammalian target of rapamycin (mTOR) is the main mediator of mitogenic stimuli transduced by PI3K/Akt. Interestingly, inhibition of mTOR activates PI3K/Akt by up-regulating IGF-1R signaling. Several targeted agents have been developed to inhibit the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Multiple pathways that contribute to the CSC properties of DCLK1HI/AcTubHI pancreatic cancer cells were identified by using whole genome transcriptome analysis [6] . Studies identified ABL1 and IGF1R to be highly expressed in DCLK1HI/AcTubHI cells, complementing ongoing preclinical and clinical evaluation of ABL1 and IGF1R pathway inhibition as new forms of targeted therapy for pancreatic cancer [38,39] . These studies suggest that both invasive and preinvasive PC may depend on DCLK1 expressing cells with cancer stem cell capabilities.…”
Section: Dclk1 and Pancreatic Cancermentioning
confidence: 80%
See 1 more Smart Citation
“…Multiple pathways that contribute to the CSC properties of DCLK1HI/AcTubHI pancreatic cancer cells were identified by using whole genome transcriptome analysis [6] . Studies identified ABL1 and IGF1R to be highly expressed in DCLK1HI/AcTubHI cells, complementing ongoing preclinical and clinical evaluation of ABL1 and IGF1R pathway inhibition as new forms of targeted therapy for pancreatic cancer [38,39] . These studies suggest that both invasive and preinvasive PC may depend on DCLK1 expressing cells with cancer stem cell capabilities.…”
Section: Dclk1 and Pancreatic Cancermentioning
confidence: 80%
“…Earlier studies have suggested that Dclk1 may mark tumor-initiating cells in a variety of tumor types [27][28][29][30][31][32][33][34][35][36][37][38][39] . DclK1 regulates several key oncogenes like c-MYC, KRAS, NOTCH1 and EMT [32,33,39] .…”
Section: Dclk1 and Pancreatic Cancermentioning
confidence: 99%
“…The PI3K/AKT pathway is activated by RTKs e.g. IR/IGF-1R which are involved in the development of different cancers including cancer of pancreas (5,15,26). AKT activates mTOR that further phosphorylates its downstream targets ribosomal protein p70 S6 kinase (S6K1) and initiation factor 4E-binding protein-1 (4E-BP1) to control transcription and translation (2,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Current targeted therapeutics have very limited effect on pancreatic cancer patients (9,(12)(13)(14). Past research has linked insulin and IGF signaling to the tumorigenesis and progression of pancreatic cancer (15,16). The PI3K/AKT/mTOR pathway is downstream of IR/IGF-1R and is associated with development and clinical aggressiveness of pancreatic cancer (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…However, except erlotinib, which is an inhibitor to epidermal growth factor receptor (EGFR), no other targeted therapy has as yet demonstrated significant effect against pancreatic cancer (9,10). Insulin-like growth factor 1 (IGF-1) and its receptor, PI3-kinase/Akt/mTOR and mitogen-activated protein kinases/extracellular signal-regulated kinases (MEK/ERK) pathway are upregulated in the majority of PDACs (11,12). However, a phase II trial on a monoclonal antibody against IGF receptor (IGFR) indicates no significant effect in OS and progression-free survival (PFS) for PDAC patients (4).…”
Section: Introductionmentioning
confidence: 99%